2005
DOI: 10.1111/j.1365-2141.2005.05619.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological identification of adult T‐cell leukaemia‐associated antigens

Abstract: SummaryAdult T-cell leukaemia (ATL) is a peripheral T-cell neoplasm caused by human T-cell leukaemia virus type I (HTLV-I). Several clinical observations suggest that some tumour-associated antigens in ATL may be recognised by the immune system. In this study, we performed the serological screening of an expression library to identify ATL-associated antigens by using materials from a unique ATL patient with long-term stable disease. Among five distinct genes isolated, serine/arginine protein kinase 1 (SRPK1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 51 publications
5
12
0
5
Order By: Relevance
“…In contrast, the ubiquitous expression pattern of SRPK1, its ability to activate a diverse array of SR protein splice factors, and our demonstration that it is increased in tumors of different origin provide a persuasive hypothesis that it serves a more global role in the missplicing observed across tumor systems. This premise is supported by a recent report by Hishizawa et al (35), showing the overexpression of SRPK1 in acute type adult T-cell leukemia (ATL) but not in chronic ATL or normal peripheral blood mononuclear cells, as well as the presence of autologous antibody to SRPK1 in the acute ATL patients. Figure 5.…”
Section: Discussionsupporting
confidence: 75%
“…In contrast, the ubiquitous expression pattern of SRPK1, its ability to activate a diverse array of SR protein splice factors, and our demonstration that it is increased in tumors of different origin provide a persuasive hypothesis that it serves a more global role in the missplicing observed across tumor systems. This premise is supported by a recent report by Hishizawa et al (35), showing the overexpression of SRPK1 in acute type adult T-cell leukemia (ATL) but not in chronic ATL or normal peripheral blood mononuclear cells, as well as the presence of autologous antibody to SRPK1 in the acute ATL patients. Figure 5.…”
Section: Discussionsupporting
confidence: 75%
“…Our current findings add a dimension in understanding diverse disease phenotypes from the prospective of regulated splicing, because dysregulation of RNA splicing has been attributed to many different kinds of human diseases (Cooper et al, 2009). Potential roles of SRPKs in cancer are underscored by the observed overexpression of SRPK1 in adult T-cell leukemia (Hishizawa et al, 2005) as well as in several types of solid tumors, such as colon, pancreatic, and breast carcinomas (Hayes et al, 2006; 2007; Plasencia et al, 2006). A more recent study demonstrated that SRPK1 is transcriptionally repressed by WT1, a well-known tumor suppressor, and overexpression of SRPK1 directly contributes to angiogenesis through induced VEGF alternative splicing that causes renal failure and Wilms’ tumors (Amin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, withdrawal of immunosuppressive agents or donor lymphocyte infusion can induce remission in relapse of ATL after allogeneic HSCT, implying the presence of a graft-versus-ATL effect. [19][20][21][22][23] Because several antigens have recently been identified as putative targets for cytotoxic T-cell responses against ATL, 38,39 future development of cellular immunotherapy targeting these molecules would reduce the incidence of relapse and improve survival in patients with residual ATL after allogeneic transplantation. Further investigations are warranted to elucidate the association between the occurrence of GVHD and disease response among allografted patients with ATL because our preliminary analysis using a similar cohort 40 Finally, the use of unrelated cord blood was associated with lower survival, most likely a result of higher treatment-related mortality.…”
Section: Discussionmentioning
confidence: 99%